Make good choices : your guide to making healthy decisions/ by Heather E. Schwartz. - Schwartz, Heather E. (Mankato, Minn. : Capstone Press, 2012)
"An introduction to making healthy choices, including the dangers of tobacco, alcohol, and drugs"--Provided by publisher.
Includes bibliographical references (p. 31) and index.
Ages 11 and up
Keywords: Decision making -- Juvenile literature